Characteristic Differences of Tidal Swamp Rice Varieties towards Methane (CH4) Emission on Peat Soil - H.L SUSILOWATI; PRIHASTO SETYANTO; R KARTIKAWATI (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2009)
Expanding the rice field area into marginal land such as peat soil could possibly obtain significant increase on greenhouse gas (GHG’s) emission. Peat soil contained large amount of organic matter. The utilization of peat soil for rice field needs pH > 3. The changes of pH will enhance the microbiology activities that produce methane (CH4). Anaerobic condition could potentially released high CH4 emission. Rice plants have beenreported to affect CH4 emission almost 90% from rice fields. Theobjective of this study is to determine the effect of characteristic differences of tidal swamp rice varieties towards CH4 emission on peat soil. A field experiment was conducted at Research Station of Indonesian Agricultural Environment Research Institute, Jakenan, Pati, Central Java, in 2006. Randomized complete design with three replications method was used to analyze four varieties of tidal swamp rice (Punggur, Tenggulang, Banyuasin, and Batanghari). 12 microplots with each has a dimension of 1.5 m x 1.5 m x 1 m were filled with peat soil from South Kalimantan. Statistical analysis of the experimental data on plant parameters were accomplished using analysis of variance (Anova). Regression and correlation analysis were also used to determine the relationship between plant parameters effected on CH4 flux. The results showed that there were significant relationship between the plant biomass, root biomass, plant tiller, plant height, and CH4 flux at 1% level of test. The relationshipbetween plant height of developed tillers were related to the proportional enhanced continuity of aerenchyma channels with the increasing plant height of rice cultivar. The CH4 emission of Punggur, Banyuasin, Tenggulang dan Batanghari were 183.01, 179.2, 124.1, and 104.0 kg ha-1, respectively. Batanghari was recomended best for transplanting under peat soil compared with others because of lower CH4 emission and no differences in grain yield. The easy way to mitigate CH4 emission from peat soil is transplanted of Batanghari.